Effect of groundwater table depth on tree stability - Lim, Eugene Yong Sheng. (2013)
Numerous research works have been done on tree stability from an arboreal point of view. However there are only few references which have attempted to explain tree stability using engineering principles. This project investigates the effect of groundwater table depth on tree stability. The shear strength of unsaturated soil is used as the primary parameter to examine the effect of foundation soil on tree stability. In this project, numerical modeling using parameters from experiments and past literatures was used to evaluate the stress distribution and deformation in the soil, the tree and its root plate. Theoretical modeling was used to simulate tree throw due to a failure slip surface in the soil. Numerical modeling has shown that an increase in depth of water table can increase the failure wind speed as much as 20% for root break failure. However, the root plate of a tree has a critical thickness in which beyond the critical thickness, the depth of water table has no influence on the tree stability. The tree is likely to fail by stock break when the thickness of the root plate exceeds the critical value. In theoretical analysis, it is discovered that a longer and thinner root plate provides the most stability for wind throw failure, assuming that the soil shears near the perimeter of the root plate. Wind throw failure in theoretical analysis is shown to be much more sensitive to variation in depth of water table compared to root break failure in numerical analysis. The failure mechanism of a tree can change as the depth of water table varies.